Modification of Screen Printed Carbon Electrode-Gold Nanoparticles (SPCE-AuNPs) for Detection of Mercury in Cosmetics - Aini, Azizah Nurul; Nurul wahidah; Putriana Dwi Agustin; Dewi Nurmarlina; Ramadhan, Syafira Elfa; Riyanto (Universitas Islam Indonesia, 2024)
The cosmetics industry in Indonesia has experienced a significant increase of 12.6% from 2022 to June 2023, with 1025 industries having a positive impact on the Indonesian economy. Apart from that, it has triggered a number of naughty manufacturers to use dangerous chemicals in their cosmetic products such as mercury (Hg). Therefore, it is important to develop a fast and sensitive method for detecting mercury in cosmetics using SPCE-AuNPs. This research was carried out by synthesizing gold nanoparticles (AuNPs) using the reducing agent sodium citrate (Na3H5C6O7) with varying concentrations and characterization of several chemical instruments. Furthermore, SPCE was modified by AuNPs, its performance and application were tested to detect mercury in cosmetic cream using cyclic voltammetry (CV). SPCE-AuNPs provides an electrochemical response with higher oxidation and reduction peaks than bare SPCE with an oxidation peak at a potential of 0.1 V to 0.3 V and a reduction peak at -0.05 V to 0.05 V at a scan rate of 0.01 V/s to 0.03 V/s. This shows a good electrochemical response so it can be used for application to detection of mercury in cosmetic samples. The SPCE modified using AuNPs can potentially be used as a sensor for mercury detection in cosmetics.